Identification of novel CYP4V2 gene mutations in 92 Chinese families with Bietti’s crystalline corneoretinal dystrophy - Meng, Xiao Hong (Mol Vis, 2014)
PURPOSE: To characterize the spectrum of CYP4V2 gene mutations in 92 unrelated Chinese probands with Bietti’s crystalline dystrophy (BCD) and to describe the molecular and clinical characteristics of four novel CYP4V2 mutations associated with BCD. METHODS: All study participants underwent a complete ophthalmological examination. Mutational screening of CYP4V2 coding regions and flanking intron sequences was examined via directional Sanger sequencing, with allele separation confirmed by screening other family members. Subsequent in silico analysis of the mutational consequence on protein function was undertaken, with the impact of the novel mutation on pre-mRNA splicing examined via RT–PCR. RESULTS: Fifteen disease-causing variants were identified in 92 probands with BCD, including four novel mutations and eleven previously reported mutations. The most prevalent mutation was c.802_810del17insGC, which was detected in 69 unrelated families, with an allele frequency of 52.7% (97/184). Homozygosity was revealed in 35 unrelated families, and compound heterozygosity was observed in 43 subjects. Four patients harbored four novel variants, with these mutations cosegregated within all affected individuals and were not found in unaffected family members and 100 unrelated controls. Transcriptional analysis of a novel splice mutation revealed altered RNA splicing. In silico analysis predicted that the missense variant, p.Tyr343Asp, disrupted the CYP4V2 surface electrostatic potential distribution and spatial conformation. Among the patients with four novel mutations, genotype did not always correlate with age at onset, disease course, or electroretinogram (ERG) changes, with phenotypic variations even noted within the same genotype. CONCLUSIONS: The c.802_810del17insCG mutation was the most common mutation in the 92 Chinese probands with BCD examined. Four novel mutations were identified, contributing to the spectrum of CYP4V2 mutations associated with BCD, with no clear link established between disease phenotype and genotype.